2017
DOI: 10.1159/000479387
|View full text |Cite
|
Sign up to set email alerts
|

Lower Airway Inflammation in Eosinophilic Chronic Rhinosinusitis as Determined by Exhaled Nitric Oxide

Abstract: Background: Chronic rhinosinusitis (CRS) is classified into eosinophilic CRS (ECRS) and non-ECRS. The objectives of this study were to evaluate lower airway inflammation by measuring the fractional concentration of exhaled nitric oxide (FeNO) and to examine the effects of endoscopic sinus surgery (ESS) on FeNO in patients with ECRS compared to non-ECRS. Methods: CRS patients with nasal polyps (23 with ECRS and 22 with non-ECRS) were enrolled into this study. ECRS was diagnosed based on the definition proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…It was likely that the observed lower sensitivity and higher specificity of total IgE reflected the higher optimal cutoff point for total IgE employed in the present study. Similar to our research, Kambara et al [40] showed that total IgE levels in patients with non-CRSwNP were significantly lower than those in patients with eCRSwNP. However, Ho et al [41] demonstrated that total serum IgE had no significant association with eCRSwNP.…”
Section: Discussionsupporting
confidence: 92%
“…It was likely that the observed lower sensitivity and higher specificity of total IgE reflected the higher optimal cutoff point for total IgE employed in the present study. Similar to our research, Kambara et al [40] showed that total IgE levels in patients with non-CRSwNP were significantly lower than those in patients with eCRSwNP. However, Ho et al [41] demonstrated that total serum IgE had no significant association with eCRSwNP.…”
Section: Discussionsupporting
confidence: 92%
“…Another important fact is that periostin better reflects chronic type 2-predominant inflammation rather than acute inflammation [19]. According to a recent study by Kambara et al [37], blood eosinophils and FeNO significantly decreased following ESS in CRSwNP [34]. Meanwhile, in patients with ICS-naïve asthma, the decreased rate of serum periostin at 24 weeks after the initiation of ICS treatment (equivalent to fluticasone propionate 400 μg daily) was numerically smaller than that of FeNO (5.4% for serum periostin vs. approximately 25% for FeNO) [38].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in patients with ICS-naïve asthma, the decreased rate of serum periostin at 24 weeks after the initiation of ICS treatment (equivalent to fluticasone propionate 400 μg daily) was numerically smaller than that of FeNO (5.4% for serum periostin vs. approximately 25% for FeNO) [38]. Serum periostin levels may not fluctuate by treatment intervention for the short term, unlike blood eosinophils and FeNO [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic allergic sinusitis has been associated with allergy to aeroallergens; however, over 80% of patients with chronic sinusitis are also sensitized to food allergens though without any difference between the groups with and without nasal polyps [24]. In eosinophilic chronic rhinosinusitis (ECRS) the inflammation extends to the lower airways, as indicated by elevated FeNO, and endoscopic sinus surgery may improve both ECRS and pulmonary dysfunction [25]. It is noteworthy that, upon chemotherapy, allergen-specific IgE levels significantly decrease, but do not disappear, suggesting that some plasma cells survive, still producing IgE [26].…”
Section: Characterization Of Subgroups Of Allergic Rhinitismentioning
confidence: 99%